Effect of varying resin content and board densities on the properties of three layers particleboard from kelempayan. / Tuan Mohd Fakrul Tuan Ismail - Tuan Ismail, Tuan Mohd Fakrul (Faculty of Applied Sciences, 2015)
The aim of this study was to investigate the use of Kelempayan species in manufacturing three layer particleboard panels. The boards were fabricated with three different densities (500 kg/m3 , 600 kg/m3 and 700 kg/m3 ). The sample also has different type of the resin content (8 %, 10 % and 12 %). The boards produced was evaluated for its modulus of rupture (MOR), modulus of elasticity (MOE), internal bond (IS), water absorption (VVA) and thickness swelling (TS) in accordance with the Japan industry Standards (JIS) A 5908:2003. The result show passed standard value based on JIS A 5908:2003 Type 13 for mechanical properties is density 600 kg/m3 with resin 12 %, the result shown in MOR (14.94 MPa) and IS (0.29 MPa). For density 700 kg/m3 with resin 8 % and 10 % only pass in MOR and IS but for resin 12 %, the all mechanical properties passed the standard value of JIS. For physical properties, only pass in thickness swelling (11.90 %) with density 600 kg/m3 and 12 % resin content. It is concluded that the boards with the density of 700 kg/m3 were able to fulfill the Japan Industry Standards specifications.